2022
DOI: 10.1051/0004-6361/202243101
|View full text |Cite
|
Sign up to set email alerts
|

The eROSITA Final Equatorial Depth Survey (eFEDS)

Abstract: Aims. The circumgalactic medium (CGM) plays an important role in galaxy evolution as the main interface between the star-forming body of galaxies and the surrounding cosmic network of in-and out-flowing matter. In this work, we aim to characterize the hot phase of the CGM in a large sample of galaxies using recent soft-X-ray observations made by SRG/eROSITA. Methods. We stack X-ray events from the 'eROSITA Final Equatorial Depth Survey' (eFEDS) around central galaxies in the 9hr field of the 'GAlaxy and Mass A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…Third, recent studies have shown that the extended hot gas atmosphere can significantly impact the total observed luminosity depending on the chosen projection radius (Nica et al 2022;Comparat et al 2022). In Comparat et al (2022) in the energy range 0.5-10 keV.…”
Section: Gas Luminosity Scaling Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, recent studies have shown that the extended hot gas atmosphere can significantly impact the total observed luminosity depending on the chosen projection radius (Nica et al 2022;Comparat et al 2022). In Comparat et al (2022) in the energy range 0.5-10 keV.…”
Section: Gas Luminosity Scaling Relationmentioning
confidence: 99%
“…Third, recent studies have shown that the extended hot gas atmosphere can significantly impact the total observed luminosity depending on the chosen projection radius (Nica et al 2022;Comparat et al 2022). In Comparat et al (2022) in the energy range 0.5-10 keV. The mean spectrum was calculated by normalizing each galaxy spectrum to its total 0.5-10 keV emission and taking the average in each energy bin.…”
Section: Gas Luminosity Scaling Relationmentioning
confidence: 99%
“…Emission from hot gas can be detected in X-rays. Comparat et al (2022) and Chadayammuri et al (2022) use eROSITA data to measure X-ray emission around stellarmass-controlled samples of star-forming and passive galaxies and find conflicting results. Comparat et al (2022) find that passive galaxies are associated with more X-ray emission while Chadayammuri et al (2022) find the opposite.…”
Section: Cool and Hot Gas In The Cgm Of Quenched Galaxiesmentioning
confidence: 99%
“…Comparat et al (2022) and Chadayammuri et al (2022) use eROSITA data to measure X-ray emission around stellarmass-controlled samples of star-forming and passive galaxies and find conflicting results. Comparat et al (2022) find that passive galaxies are associated with more X-ray emission while Chadayammuri et al (2022) find the opposite. Chadayammuri et al (2022) argue that the discrepancy is driven by differences in how emission from groups and clusters is treated for galaxies other than the group and cluster centrals.…”
Section: Cool and Hot Gas In The Cgm Of Quenched Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation